1998
DOI: 10.1021/jp973404v
|View full text |Cite
|
Sign up to set email alerts
|

The New Wave in Shock Waves

Abstract: Laser-driven shock waves (0−5 GPa) can be generated at high repetition rates (100/s) using a moderate-energy tabletop picosecond laser system and a multilayered microfabricated shock target array. High spatial resolution is needed to obtain high temporal resolution of the effects of a steeply rising shock front on molecular materials. The needed spatial resolution is obtained using a sandwich arrangement with a thin layer of sample material termed an “optical nanogauge”. Experiments with an anthracene nanogaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
53
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…Shock wave physics is becoming yet another fertile area for atomistic studies. Laser-driven shock waves through samples tens or hundreds of nanometers thick can be probed by spectroscopy [3] or interferometry [4] with picosecond time resolution, time and length scales well within the capabilities of modern MD simulations [5].Previous studies of shock waves in 3D solids have primarily considered fcc Lennard-Jonesium with shocks traveling in the ͗100͘ direction [5][6][7]. An important first step to extending these simulations toward more realistic materials, which may include preexisting defects, dislocations, and grain boundaries, is the study of orientation-dependent effects on shock propagation in single crystals.…”
mentioning
confidence: 99%
“…Shock wave physics is becoming yet another fertile area for atomistic studies. Laser-driven shock waves through samples tens or hundreds of nanometers thick can be probed by spectroscopy [3] or interferometry [4] with picosecond time resolution, time and length scales well within the capabilities of modern MD simulations [5].Previous studies of shock waves in 3D solids have primarily considered fcc Lennard-Jonesium with shocks traveling in the ͗100͘ direction [5][6][7]. An important first step to extending these simulations toward more realistic materials, which may include preexisting defects, dislocations, and grain boundaries, is the study of orientation-dependent effects on shock propagation in single crystals.…”
mentioning
confidence: 99%
“…Some sophisticated applications of laser spectroscopy to in situ observation of shock-induced phenomena have been reported over the last couple of decades. [1][2][3][4][5][6] In this paper we report shock-induced changes in vibrational spectra of benzene, iodobenzene, and nitrobenzene measured by a single-pulse laser Raman spectrometer in conjunction with a plate impact technique. It was found that shock-induced changes in Raman spectra of nitrobenzene are quite different from those of benzene and iodobenzene.…”
mentioning
confidence: 99%
“…The probe pulses interrogate a region of ϳ20 mm in diameter at the center of the ϳ100 mm diameter nanoshock [9]. In this central region, the pressure and velocity at the nanoshock front remain constant for several nanoseconds [1,9,10], showing we are observing compression by an approximately planar shock front.…”
mentioning
confidence: 95%
“…The BSA film is a crude model for a dry biological tissue such as skin. The nanoshock technique and the laser apparatus have been discussed previously [1,9,10]. A schematic of the experiment is shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation